THE EFFECT OF SEA SURFACE TEMPERATURE ON SMALL PELAGIC FISH CATCHES IN WPP 573 - GILANG MAULANA; Raymundus Putra Situmorang; Yosy Gustasya (Universitas Mataram, 2026)
Sea surface temperature (SST) is a key oceanographic parameter influencing the distribution and abundance of small pelagic fish in tropical waters. This study aims to analyze the effect of SST on small pelagic fish catches in Fisheries Management Area (FMA) 573. Catch data were obtained from the Fisheries Resource Center of Indonesia (FRCI) for the 2015–2021 period, while SST data were derived from Aqua MODIS satellite imagery with 4 km resolution, processed using Seadas 7.4 software. A simple linear regression was applied to examine the relationship between SST and fish catches. The results indicate a negative relationship, where each 1 °C increase in SST tends to reduce catches by approximately 35 thousand tons. The coefficient of determination (R²) of 0.531 shows that 53.1% of the catch variability is explained by SST, while the remaining is influenced by other factors such as primary productivity (chlorophyll-a), upwelling intensity, global climate phenomena (ENSO, IOD), and fishing pressure. These findings highlight SST as an important indicator for predicting fishing seasons in FMA 573 and emphasize the need to integrate satellite-based oceanographic data into Ecosystem-Based Fisheries Management (EBFM) to ensure sustainable fisheries in Indonesian tropical waters.